An Overview of The Side Effects of Covid-19 Booster Vaccination at Adults in Sampih Village, Wonopringgo District - Wulandari, Ajeng; Izzah, Nur (Prosiding University Research Colloquium, 2023)
Booster vaccination is very necessary for the community to avoid COVID-19; however, this booster can cause side effects. Therefore, this needs to be anticipated so that these side effects do not cause problems. This study aims to obtain the side effects of Booster Covid- 19 vaccination at adults. A total of 46 respondents were selected using the cluster sampling technique. This study applied a descriptive design of data collection using a check list. The results stated that all (100%) booster vaccine users get side effects, the booster used here are Moderna, Sinovac, and Pfizer. It could be concluded all respondents have effect sides.